Antecedents of student satisfaction: the role of student perceived service quality / Peter Sin Howe Tan, Yuen Onn Choong and I-Chi Chen - Tan, Peter Sin Howe; Choong, Yuen Onn; Chen, I-Chi (Universiti Teknologi MARA, 2021)
There is a lack of attention from past studies on the role of antecedents in the private higher education in Malaysia. Thus, this paper aims to examine the roles of reliable information and past experience on perceived service quality and satisfaction among the undergraduate students of private universities in Malaysia. A self-administered questionnaire was adopted and collected 388 valid data from the 9 private universities in Malaysia. The SERVPERF instrument was adopted to evaluate the perceived service quality among the undergraduate students. The PLS-SEM was applied to analyze the students’ responses in determining the role of antecedents in improving student satisfaction by providing quality tertiary education in the private universities. The findings depicted that reliable information is significantly related with student perceived service quality. However, there is no relationships between past experience and student perceived service quality. Student perceived service quality is found significantly related to student satisfaction. This paper provides a valuable contribution in the body of knowledge of the antecedent and consequence of perceived service quality. The findings of the study help the management of the universities to improve the student satisfaction through the focus on the role of antecedents, particularly reliable information. Several implications are offered which would benefits Malaysia private universities and Ministry of Higher Education.